2010
DOI: 10.1002/cbf.1618
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cardiovascular cell function by hydrogen sulfide (H2S)

Abstract: Since the discovery of endogenously-produced hydrogen sulfide (H 2 S) in various tissues, there has been an explosion of interest in H 2 S as a biological mediator alongside other gaseous mediators, nitric oxide and carbon monoxide. The identification of enzymeregulated H 2 S synthetic pathways in the cardiovascular system has led to a number of studies examining specific regulatory actions of H 2 S. We review evidence showing that endogenously-generated and exogenously-administered H 2 S exerts a wide range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(88 citation statements)
references
References 83 publications
0
80
0
8
Order By: Relevance
“…In early studies, H 2 S was found to facilitate the induction of hippocampal long-term potentiation by enhancing the activity of NMDA receptors in neurons (10). It also enhances NO-induced relaxation of vascular and intestinal smooth muscles (11) and inhibits high K + -induced corticotropine secretion from hypothalamic slices (12 (5,9,14). In contrast, exposure to H 2 S is reported to facilitate apoptotic cell death in aortic smooth muscle cells, lung fibroblasts, and pancreatic acinar cells (13).…”
Section: H 2 S As a Gasotransmittermentioning
confidence: 99%
See 1 more Smart Citation
“…In early studies, H 2 S was found to facilitate the induction of hippocampal long-term potentiation by enhancing the activity of NMDA receptors in neurons (10). It also enhances NO-induced relaxation of vascular and intestinal smooth muscles (11) and inhibits high K + -induced corticotropine secretion from hypothalamic slices (12 (5,9,14). In contrast, exposure to H 2 S is reported to facilitate apoptotic cell death in aortic smooth muscle cells, lung fibroblasts, and pancreatic acinar cells (13).…”
Section: H 2 S As a Gasotransmittermentioning
confidence: 99%
“…H 2 S seems to contribute to the pathogenesis of several diseases, including Alzheimer's disease, hypertension, and cardiac infarction (4,9,32). Therefore, modulation of its production may be a potential therapeutic strategy for these diseases.…”
Section: H 2 S and Diabetes Mellitusmentioning
confidence: 99%
“…Excitement over this molecule, from basic research to translational medicine, has spawned nearly as many reviews as primary research articles (cf. 17,24,32,38,44,49,55,56,68,79). In many instances H 2 S seems to fit the criteria for a ''gasotransmitter'' as adapted from the wellknown criteria for neurotransmitters by Wang (74); i.e., gasotransmitters must 1) be a small molecule of gas, 2) be freely membrane permeable, 3) be endogenously and enzymatically generated in a regulated manner, 4) have well-defined specific functions at physiologically relevant concentrations, and 5) act on specific cellular targets.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological importance of H 2 S is gaining acceptance with respect to its beneficial effects on various aspects of cardiovascular pathophysiology (1,2). Cell culture studies report that H 2 S supplementation can decrease oxidative stress and the secretion of proinflammatory cytokines, such as MCP-1 and IL-8, and activate insulin signaling pathways using monocytes (3), endothelial cells (4), and adipocytes (5).…”
mentioning
confidence: 99%